The families Malachiidae and Dasytidae in the collections of the Goulandris Natural History Museum, Athens, Greece - Mirutenko, Vladyslav V. (ENTOMOLOGIA HELLENICA, 2013)
Entomological collections of the Goulandris Natural History Museum in Athens were reviewed. Eleven species of the family Malachiidae and six species of the family Dasytidae (Insecta: Coleoptera) were identified in the collections of the museum. A species list is provided, where the locations and dates of findings, as well as the distribution of each species and short comments are given.